Analysis of Silt Dam System Grade and Joint Regulation in Typical Small Watershed of Loess Plateau. Issue 1 (June 2020) - Sun, Weiying; Zhang, Pan
Abstract: When a silt dam system is formed, its function of flood detention and erosion reduction is not simply superimposed. The transport and transfer process of sediment between the dams system presents a nonlinear relationship, which we call the grade regulation function of the dam system. In order to study the mechanism of joint action and regulation of flood storage and sediment retention in silt dam systems in small watersheds, the Yulingou small watershed silt dam system in the first sub-region of the hilly and gully region of the Loess Plateau was taken as the research area. Based on the systematic analysis of different dam levels and different grading ways (series, parallel and mixed), the silt retention and sediment retention effect of silt dams in small watershed of the Loess Plateau is analysed. The spatial distribution model reveals the control relationship between the dam system and channel unit dam on the flood and cement sand in different layers, and clarifies the grade effect of the flood and sediment storage capacity of the small watershed. The results show that the reasonable arrangement of silt dam system in small watershed can effectively extend the service life of main dam, the reasonable arrangement of different types of dam system can extend the service life to different degrees, and the joint application of cascade dam system can realize the internal digestion of flood and sediment.